2006
DOI: 10.1590/s0100-40422006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa do fluxo de amônia na interface ar-mar na Baía de Guanabara: estudo preliminar

Abstract: ) were measured in surface waters of the Guanabara Bay. Concentrations varied from 2 to 143 μmol L -1 . Ammonia exchange at the air-sea interface was quantified using a numerical model. No measurement of NH 3 concentration in air (c air ) was performed. Thus, calculations of NH 3 flux were based on the assumptions of c air = 1 and 5 μg m -3 . Fluxes were predominantly from the water to the atmosphere and varied from -20 to almost 3500 μg N m -2 h -1 .Keywords: ammonia; air-sea exchange; Guanabara Bay. 14,15 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
6
0
6
Order By: Relevance
“…The negative correlation of NH 4 + with salinity also corroborates this hypothesis, since the nitrification is an aerobic process of biological oxidation of NH 4 + followed by the oxidation of NO 2 to NO 3 -, performed by specific groups of autotrophic bacteria. One part of this NH 4 + can be also emitted to the atmosphere, since a previous study at Guanabara Bay quantified the emissions of NH 4 + from water to the atmosphere and showed that these emissions were particularly important nearly of the most polluted regions of the bay, including the northwest area (Guimarães & Mello, 2006). Anyway the transect 1 showed a tendency to sub-oxic conditions (DO between 20-40% of saturation).…”
Section: Discussionmentioning
confidence: 98%
“…The negative correlation of NH 4 + with salinity also corroborates this hypothesis, since the nitrification is an aerobic process of biological oxidation of NH 4 + followed by the oxidation of NO 2 to NO 3 -, performed by specific groups of autotrophic bacteria. One part of this NH 4 + can be also emitted to the atmosphere, since a previous study at Guanabara Bay quantified the emissions of NH 4 + from water to the atmosphere and showed that these emissions were particularly important nearly of the most polluted regions of the bay, including the northwest area (Guimarães & Mello, 2006). Anyway the transect 1 showed a tendency to sub-oxic conditions (DO between 20-40% of saturation).…”
Section: Discussionmentioning
confidence: 98%
“…A própria água da chuva pode carrear amônia (Migon et al 1991, Lima et al 2009), especialmente em áreas urbanas (Ugucione et al 2002) (Ugucione et al 2002), constituindo uma fonte adicional para o aumento destes compostos nos ecossistemas aquáticos. As estimativas de emissão de amônia à atmosfera na Lagoa Rodrigo de Freitas nos dias chuvosos foram altas, uma vez que superaram cerca de cinco vezes aqueles encontrados na Baia da Guanabara, que se localiza a poucos km da Lagoa, com elevada carga de esgotos (Guimaraes & de Mello 2006). Nesse sentido, os dias secos apresentaram inclusive valores de fluxo negativo, indicando entrada de N atmosférico para a superfície da água e confirmando este potencial da chuva sobre o aporte alóctone de N amoniacal.…”
Section: Discussionunclassified
“…Apesar desta potencial importância ecológica associada à alta capacidade de dispersão da amônia na atmosfera , ainda são escassos os estudos sobre as emissões deste composto pelos ecossistemas aquáticos (Guimaraes & De Mello 2006), especialmente ao longo de escalas de tempo de curta duração. O objetivo desse estudo foi avaliar as variações de curto prazo entre cinco dias consecutivos e na escala espacial intra-lagunar nas emissões de amônia de uma lagoa costeira tropical urbana (Lagoa Rodrigo de Freitas) à atmosfera.…”
Section: Introductionunclassified
“…A distribuição das estações de amostragem, as trajetórias realizadas por data de coleta e a descrição dos procedimentos adotados para coleta de amostras de água, bem como das medições de pH, condutividade e temperatura realizadas in situ, encontram-se em Guimarães e de Mello. 9 Amostras de ar atmosférico foram coletadas somente em 6 das 37 estações de amostragem para quantificação de N 2 O na água. Para isso, aproximadamente 20 mL de ar atmosférico foram coletados e armazenados em seringas (Embramac) de polipropileno de 60 mL vedadas por meio de torneiras plásticas de 3 vias.…”
Section: Coletas E Tratamento De Amostrasunclassified